2019
DOI: 10.1186/s12889-019-7236-9
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity is an important risk factor for type 2 diabetes: a case-control study of new referrals to the University clinics, Shiraz, Southern Iran

Abstract: Background The prevalence of food insecurity (FI) as “the limited or uncertain availability of enough food for an always active and healthy life” and diabetes as “the most common metabolic disease” are rising in Iran. The aim was to assess the FI, depression, and socioeconomic status as risk factors for type 2 diabetes (T2D). Methods This case-control study was conducted on 135 patients with T2D as cases (99 females, 36 males, mean age 46.83 years) and 135 subjects with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 48 publications
2
19
0
1
Order By: Relevance
“…Literature has shown that food insecurity is an important risk factor for type 2 diabetes. [28] People with diabetes are more dependent on the regularity of food and medicine and therefore this may have caused the perceived risk of food and drug shortage. Concurrently, a higher proportion of individuals with diabetes reported an increase in smoking and drinking than those without diabetes in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Literature has shown that food insecurity is an important risk factor for type 2 diabetes. [28] People with diabetes are more dependent on the regularity of food and medicine and therefore this may have caused the perceived risk of food and drug shortage. Concurrently, a higher proportion of individuals with diabetes reported an increase in smoking and drinking than those without diabetes in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Another research demonstrated that the prevalence of food insecurity in the villagers of Nishabur (Iran) was 40.9%, which was significantly correlated with the education level and age of the household head, as well as the possession of a home and car, presence of chronic diseases in a family member, presence of a smoker in the family, distance from cities, and income status [17]. In the aforementioned studies, the methods applied for the assessment of food insecurity prevalence and the influential factors [15][16][17], as well as some other experiments [18][19][20][21][22][23][24][25][26][27][28][29][30], are almost similar to the current research, which also confirms our findings.…”
Section: Resultsmentioning
confidence: 99%
“…According to recent meta-analysis, general food insecurity prevalence has been reported by 49% among Iranian households (2). Food insecurity is strongly associated with poorer health outcomes (3,5). Several studies have demonstrated associations between food insecurity and overweight/obesity among children and adults using both self-reported and objective measures of body mass index (BMI) (6,7).…”
Section: Introductionmentioning
confidence: 99%